A scalable decentralized system for fair token distribution and seamless users onboarding - Francesco Bruschi; Manuel Tumiati; Vincenzo Rana; Mattia Bianchi; Donatella Sciuto (Blockchain: Research and Applications, 2022)
Tokens are digital, transferable, and programmable assets and one of the most promising tools offered by blockchains. They could enable a wide range of applications, from down to earth to futuristic. One of the main issues in achieving wide adoption of tokens is onboarding: main platforms require users to deal with specific tools such as wallets, transaction fees, key generation, and storage.The most common solution to offer a familiar experience to naive users are custodial intermediaries, which have the important drawback of centralizing the process, and keeping users away from the advantages of self-sovereign assets control.In this paper, we present a process for the distribution of digital tokens to end users, exploiting “physical” objects for initial distribution. The process is aimed at making the onboarding of users not yet accustomed to blockchain tools and concepts as easy as possible, in a secure and decentralized way.